CHEMICAL COMPOSITION OF HORSERADISH AND ITS USE IN THE TREATMENT OF SOME DISEASES (Scientific journal of the Fergana State University, 2023)
The article describes the botanical characteristics of the horseradish plant, the minerals it contains, the nutritional value of organic compounds, as well as the structure of biologically active chemical compounds in the treatment of ARVI (acute respiratory viral infection) and influenza. additional information on human health, some information on the use of horseradish in modern medicine and folk medicine.